Electrochemical CO2 reduction to ethanol: Synergism of (n-Bu4N)3SVMo11O40 and an In catalyst. (20th March 2023) - Sun, Wencong; Tai, Yuehua; Tian, Wenxue; Zhou, Li; Li, Chunxiang
Abstract: The synthesis of ethanol by electrochemical CO2 reduction is attractive because CO2 is one of the key synthons in organic synthesis for the chemical and fuel industries. However, the reactions of electrochemical CO2 reduction to ethanol have the limitations of lower Faraday efficiency (FE) and insufficient understanding of the mechanisms. Herein, we reported the synergism of commercial indium (In) catalysts and a polyoxometalate electrolyte, i.e., (n-Bu4 N)3 SVMo11 O40 for ethanol generation (FE 69.5%) by the electrochemical reduction of CO2 . In-depth characterizations and computational studies of the In-based materials indicated that CC coupling caused the generation and consumption of oxygen vacancies in situ formed In2 O3, where In acted as the active sites. The polyoxometalate electrolyte induced multiple proton-coupled electron transfers via Mo VI/IV in the H2n SV V Mo IV n Mo VI 11-n O40 3− species for enhanced ethanol selectivity.